2014
DOI: 10.3109/14767058.2014.900039
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and antioxidant enzyme levels in blood of respiratory distress syndrome – Egyptian preterms and their mothers

Abstract: The existence of oxygen metabolites and lipid peroxidation was significantly more obvious in RDS preterms and in their mothers than those without.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…have been inconclusive regarding the SOD antioxidant activity. Some authors have observed a decrease of levels or activities of SOD in preterm neonates compared with controls (36,39). However, other studies reported an increase (40) or the absence of significant differences in SOD between premature and term newborns (41,42).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…have been inconclusive regarding the SOD antioxidant activity. Some authors have observed a decrease of levels or activities of SOD in preterm neonates compared with controls (36,39). However, other studies reported an increase (40) or the absence of significant differences in SOD between premature and term newborns (41,42).…”
Section: Discussionmentioning
confidence: 98%
“…Although it was reported that GPx activity increased in preterm infants vs. term infants (42), many other studies have evidenced a deficiency in the glutathione system in preterm newborns (51). Clifford and Lovina (52) and other authors have shown lower GPx activities in preterm infants relative to term neonates, especially in those preterm infants with OxS-related neonatal morbidities (36,39). Ochoa et al (53) also observed lower cytosolic GPx activity, associated with higher levels of hydroperoxides in erythrocyte membranes, among a group of preterm infants a 72 h after birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there are considerable variations in the contribution of vasoactive substances to endothelium-dependent relaxations in different tissues-it appears that nitric oxide (NO) is the principal vasodilator in conduit arteries, whereas other mediators, such as endothelialderived hyperpolarising factors (EDHF), make a significant contribution at the level of the resistance arteries [47,48]. Despite this clear role for other mediators, NO is the most extensively studied vasodilator in the preterm newborn [49][50][51][52][53], partly due to its therapeutic use for the treatment of persistent pulmonary hypertension of the newborn.…”
Section: Vasodilatationmentioning
confidence: 99%